The Effect of Red Bean Flour (Phaseolus Vulgaris L.) and Green Spinach (Amaranthus L) Addition on the Organoleptic and Chemical Quality (Protein and Iron) Tests of Pancakes as a Snack Meal - Cantika Putri Aisyah Nasution; Abdul Hairuddin Angkat (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
Pancakes are a popular snack among people and are usually enjoyed as an alternative to breakfast. Original pancakes are flat, round and thin cakes. Original pancakes contain 160 kcal of energy nutrients, 7 grams of fat and 4 grams of protein. Original pancakes still lack nutrients in the form of protein and iron. To add nutrients to the pancakes, a new formula was created, namely red bean and green spinach pancakes. The aim of the research was to determine the effect of adding red bean flour and green spinach powder on the physical quality and chemical quality of pancakes as a snack. The design and type of this research was experimental with a completely randomized design (CRD) with 3 treatments and 2 repetitions, namely Formulation A, 35 gr red bean flour and 25 gr green spinach, Formulation B, 30 gr red bean flour and 20 gr green spinach, Formulation C,  red bean flour  25 gr and green spinach 25 gr. Data collection procedures were carried out using organoleptic tests and chemical tests. Organoleptic tests were carried out on somewhat trained panelists, namely 50 nutrition students. Analysis of the physical quality and chemical quality of pancakes includes color, texture, taste, aroma, protein and iron. The results of research on organoleptic tests showed that the most preferred pancakes are 30 gr red bean flour pancakes and 20 gr green spinach (formulation B) in terms of color (3.58), texture (3.62), taste (3.68), aroma (3.39). Meanwhile, in chemical tests it can be seen that the nutritional content of red bean and green spinach flour pancakes is protein (8.78 gr) and iron (4.252 gr/mg).Conclusion based on the results of organoleptic tests the preferred formulation is formulation B 30 gr of red bean flour and 20 gr of green spinach and the chemical quality of protein (8.78 gr) and iron (4.252 gr/mg).